Efficacy and Safety of Dual Antiplatelet Therapy After Complex PCI - Giustino, Gennaro; Chieffo, Alaide; Palmerini, Tullio; Valgimigli, Marco; Feres, Fausto; Abizaid, Alexandre; Costa, Ricardo A; Hong, Myeong-Ki; Kim, Byeong-Keuk; Jang, Yangsoo; Kim, Hyo-Soo; Park, Kyung Woo; et al. (Journal of the American College of Cardiology, 2016)
Optimal upfront dual antiplatelet therapy (DAPT) duration after complex percutaneous coronary intervention (PCI) with drug-eluting stents (DES) remains unclear. This study investigated the efficacy and safety of long-term (≥12 months) versus short-term (3 or 6 months) DAPT with aspirin and clopidogrel according to PCI complexity. The authors pooled patient-level data from 6 randomized controlled trials investigating DAPT durations after PCI. Complex PCI was defined as having at least 1 of the following features: 3 vessels treated, ≥3 stents implanted, ≥3 lesions treated, bifurcation with 2 stents implanted, total stent length >60 mm, or chronic total occlusion. The primary efficacy endpoint was major adverse cardiac events (MACE), defined as the composite of cardiac death, myocardial infarction, or stent thrombosis. The primary safety endpoint was major bleeding. Intention-to-treat was the primary analytic approach. Of 9,577 patients included in the pooled dataset for whom procedural variables were available, 1,680 (17.5%) underwent complex PCI. Overall, 85% of patients received new-generation DES. At a median follow-up time of 392 days (interquartile range: 366 to 710 days), patients who underwent complex PCI had a higher risk of MACE (adjusted hazard ratio [HR]: 1.98; 95% confidence interval [CI]: 1.50 to 2.60; p < 0.0001). Compared with short-term DAPT, long-term DAPT yielded significant reductions in MACE in the complex PCI group (adjusted HR: 0.56; 95% CI: 0.35 to 0.89) versus the noncomplex PCI group (adjusted HR: 1.01; 95% CI: 0.75 to 1.35; p = 0.01). The magnitude of the benefit with long-term DAPT was progressively greater per increase in procedural complexity. Long-term DAPT was associated with increased risk for major bleeding, which was similar between groups (p = 0.96). Results were consistent by per-treatment landmark analysis. Alongside other established clinical risk factors, procedural complexity is an important parameter to take into account in tailoring upfront duration of DAPT.